Impact of Dietary Modifications on Plasma Sirtuins 1, 3 and 5 in Older Overweight Individuals Undergoing 12-Weeks of Circuit Training - Wasserfurth, Paulina; Nebl, Josefine; Rühling, Miriam Rebekka; Shammas, Hadeel; Bednarczyk, Jolanthe; Koehler, Karsten; Boßlau, Tim Konstantin; Krüger, Karsten; Hahn, Andreas; Das, Anibh Martin (Basel : MDPI, 2021)
Sirtuins are nicotinamide adenine dinucleotide (NAD+)-dependent deacetylases that regulate numerous pathways such as mitochondrial energy metabolism in the human body. Lower levels of these enzymes were linked to diseases such as diabetes mellitus and were also described as a result of aging. Sirtuins were previously shown to be under the control of exercise and diet, which are modifiable lifestyle factors. In this study, we analyzed SIRT1, SIRT3 and SIRT5 in blood from a subset of healthy elderly participants who took part in a 12-week randomized, controlled trial during which they performed, twice-weekly, resistance and aerobic training only (EX), the exercise routine combined with dietary counseling in accordance with the guidelines of the German Nutrition Society (EXDC), the exercise routine combined with intake of 2 g/day oil from Calanus finmarchicus (EXCO), or received no treatment and served as the control group (CON). In all study groups performing exercise, a significant increase in activities of SIRT1 (EX: +0.15 U/mg (+0.56/−[−0.16]), EXDC: +0.25 U/mg (+0.52/−0.06), EXCO: +0.40 U/mg (+0.88/−[−0.12])) and SIRT3 (EX: +0.80 U/mg (+3.18/−0.05), EXDC: 0.95 U/mg (+3.88/−0.55), EXCO: 1.60 U/mg (+2.85/−0.70)) was detected. Group comparisons revealed that differences in SIRT1 activity in EXCO and EXDC differed significantly from CON (CON vs. EXCO, p = 0.003; CON vs. EXDC, p = 0.010). For SIRT3, increases in all three intervention groups were significantly different from CON (CON vs. EX, p = 0.007; CON vs. EXDC, p < 0.001, CON vs. EXCO, p = 0.004). In contrast, differences in SIRT5-activities were less pronounced. Altogether, the analyses showed that the activity of SIRT1 and SIRT3 increased in response to the exercise intervention and that this increase may potentially be enhanced by additional dietary modifications.